An economic analysis of the philosophical common good. Issue 8 (8th August 2016) - Murphy, Tim; Parkey, Jeff
Abstract : Purpose: The purpose of this paper is to analyze economically several versions of the philosophical common good in order to contribute to the search for a viable conceptualization of the common good. Design/methodology/approach: The paper presents an economic analysis of the common good by examining the extent to which eight different versions of the philosophical concept possess the consumption characteristics of excludability and rivalry – and thus how each version may be classified as an economic good: private, public, common, or club. Findings: One of the examined versions of the philosophical common good is an economic common good; three versions are club goods; and four versions are public goods. Only those versions of the common good that are classifiable as public goods merit consideration as adequate conceptualizations in political and philosophical thought. In assessing the admissible versions we conclude that a viable conceptualization of the common good may simply be the maintenance of a peaceful social order that allows people to pursue their individual and collective goals in community. Originality/value: The article shows that an analysis of the philosophical common good using the economic criteria of excludability and rivalry can contribute to common good discourse.